Educational Relationship from the Perspective of Selected Anthropological Conceptions - Jeziorański, Marek (Paedagogia Christiana, 2015)
The article is a theoretical search for the meaning of the term “educational relationship” in reference to selected anthropological assumptions. The main research problem is the question about the development of the meaning/description/definition of “educational relationship” in regard to various concepts of the human being theory. In order to answer this question, the first part presented “relationship” in general. At this stage, mostly philosophical analyses were applied. The next part showed a network of problem issues conditioning the understanding of “relationship”, and the last one submitted selected anthropological conceptions and their repercussions for the understanding of “educational relationship”.